Interactions between landscape changes and host communities can regulate Echinococcus multilocularis transmission - GIRAUDOUX, P.; CRAIG, P. S.; DELATTRE, P.; BAO, G.; BARTHOLOMOT, B.; HARRAGA, S.; QUÉRÉ, J.-P.; RAOUL, F.; WANG, Y.; SHI, D.; VUITTON, D.-A. (Parasitology, 2003)
An area close to the Qinghai-Tibet plateau region and subject to intensive deforestation contains a large focus of human alveolar echinococcosis while sporadic human cases occur in the Doubs region of eastern France. The current review analyses and compares epidemiological and ecological results obtained in both regions. Analysis of rodent species assemblages within quantified rural landscapes in central China and eastern France shows a significant association between host species for the pathogenic helminth Echinococcus multilocularis, with prevalences of human alveolar echinococcosis and with land area under shrubland or grassland. This suggests that at the regional scale landscape can affect human disease distribution through interaction with small mammal communities and their population dynamics. Lidicker's ROMPA hypothesis helps to explain this association and provides a novel explanation of how landscape changes may result in increased risk of a rodent-borne zoonotic disease.